Consumer engagement of The Wildlife Trusts’ experiential campaign 30 Days Wild, and its contribution to organisational objectives - Shutt, Jennifer (2016)
This project describes The Wildlife Trusts (TWT) and the strategic question that remains unknown in regard to the effectiveness of their 30 Days Wild (30DW) experiential campaign.